2022
DOI: 10.1007/s11523-022-00868-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Epidermal Growth Factor Receptor Exon 20 Insertion Mutations in Non-small-Cell Lung Cancer in Europe: A Pragmatic Literature Review and Meta-analysis

Abstract: Background Information on the epidemiology of uncommon EGFR mutations including exon 20 insertions amongst nonsmall-cell lung cancer (NSCLC) is lacking. Objective The objective of this pragmatic literature review (PLR) and meta-analysis was to generate robust prevalence and incidence estimates based on ranges of exon 20 insertion mutations reported in the literature. Materials and methods Searches of MEDLINE, Embase, congresses and reference lists for articles published from 2013 in key European countries of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…In this real‐world analysis using three US NGS genomic datasets, EGFR ex20ins variants account for ~ 1% of all NSCLC cases in each of the three databases. The estimated frequency of ex20ins was ~ 7–8% of all EGFRm lung adenocarcinomas, which is consistent with the range (up to 12%) reported in the literature from other US‐based databases [ 13 ] and globally [ 2 , 17 , 18 , 19 , 20 ]. The near loop was the most frequent insertion region of EGFR ex20ins, where ~ 70% of all insertions were found.…”
Section: Discussionsupporting
confidence: 88%
“…In this real‐world analysis using three US NGS genomic datasets, EGFR ex20ins variants account for ~ 1% of all NSCLC cases in each of the three databases. The estimated frequency of ex20ins was ~ 7–8% of all EGFRm lung adenocarcinomas, which is consistent with the range (up to 12%) reported in the literature from other US‐based databases [ 13 ] and globally [ 2 , 17 , 18 , 19 , 20 ]. The near loop was the most frequent insertion region of EGFR ex20ins, where ~ 70% of all insertions were found.…”
Section: Discussionsupporting
confidence: 88%
“…Insertional mutations, that is, mutations in the DNA strand caused by the insertion of additional nucleotides or DNA fragments [ 30 ]. Insertion mutations occur from time to time, and in humans, exon 20 insertion mutations lead to an increased prevalence of non-small-cell lung cancer (NSCLC) [ 31 ]; in the medaka fish ( Oryzias latipes ), intra-exon insertion of an additional 1.9 kb fragment resulted in oculocutaneous albinism [ 32 ]; in human neonatal fetuses, we found that FGFR3 insertions resulted in shortened extremities, curved femurs, and narrowed thorax. This mutation also leads to overexpression of Fgfr3 in zebrafish, resulting in downstream signaling and overactivation of the dorsal embryo [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies suggested that CLN-081 was a more selective inhibitor in comparison with poziotinib and osimertinib in vitro [53]. A multicenter, phase I/IIa trial accessed 73 evaluable patients and the interim results revealed an ORR of 38.4% (28/73),a DCR of 95.9% (70/73), and a median PFS of 10 months (6)(7)(8)(9)(10)(11)(12). Of note, CLN-081 presented encouraging efficacy in patients who received prior EGFR exon 20 insertion inhibitors, as two patients obtained partial response and two patients obtained stable disease.…”
Section: Cln-081 (Tas6417)mentioning
confidence: 99%